2022
DOI: 10.3390/genes13071168
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Diseases: Insights from Transcriptomics Studies

Abstract: Results of expression studies can be useful to clarify the genotype-phenotype relationship. However, according to data from recent literature, there is a large group of genes that are revealed as differentially expressed (DE) in many studies, regardless of the biological context. Additional analyses could shed more light on the relationships between genes, their differential expression, and diseases. We generated a set of 9972 disease genes from five gene-phenotype databases (OMIM, ORPHANET, DDG2P, DisGeNet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…2020 ). Essential-for-life genes, which also showed an increased excess of rare HI variants in severe COVID-19, are enriched in genes intolerant to HI variants and disease genes ( Dickinson et al, 2016 ), which are often overexpressed in disease-related tissues and exhibit high levels of network connectivity ( Kolobkov et al, 2022 ). We can hypothesize that essential genes can be mutually regulated with more genes with fewer steps required to influence the core genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020 ). Essential-for-life genes, which also showed an increased excess of rare HI variants in severe COVID-19, are enriched in genes intolerant to HI variants and disease genes ( Dickinson et al, 2016 ), which are often overexpressed in disease-related tissues and exhibit high levels of network connectivity ( Kolobkov et al, 2022 ). We can hypothesize that essential genes can be mutually regulated with more genes with fewer steps required to influence the core genes.…”
Section: Discussionmentioning
confidence: 99%
“…Our next approach was to analyze the lists of genes associated with human diseases affecting certain organs and systems. We used our previously constructed gene list of disease genes described in detail elsewhere ( Kolobkov et al, 2022 ). Shortly, we generated a set of 9,972 genes from five gene-phenotype databases (OMIM, ORPHANET, DDG2P, DisGeNet and MalaCards) and a report of the IUIS.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main differences between core and peripheral genes in our study was the significantly lower number of tissue-specific genes among peripheral genes. It has been shown that disease-causing genes are often tissue-specific and, in a healthy state, are expressed at a higher level in those tissues that are affected in pathology [ 33 , 53 , 54 ]. In this context, one of the possible explanations for why biologically important peripheral genes from the near-core FPs remain peripheral is their low tissue specificity.…”
Section: Discussionmentioning
confidence: 99%
“…We next compared these three sets of genes for the number of genes that may be biologically important in relation to the development and course of acute infection. As biologically important, we considered the following gene groups: haploinsufficient [31], essential for life [32], intolerant to loss-offunction variants and intolerant to missense variants (https://storage.googleapis.com/ gnomadpublic/release/2.1.1/constraint/gnomad.v2.1.1.lof_metrics.by_gene.txt.bgz (accessed on 21 June 2022)), linked to SARS-CoV-2 infection and/or COVID-19 disease from the GENCODE project (https://www.gencodegenes.org/human/covid19_genes.html# (accessed on 12 May 2023)), and immune tissue-specific [33]. Other tissue-specific or nonspecific genes were included in the analysis for the comparison with immune tissuespecific genes.…”
Section: Theoretical Phase: Gene List Constructionmentioning
confidence: 99%
“…High-throughput technologies continue to produce vast quantities of molecular data, be it genomic, transcriptomic, proteomic, or otherwise. These different omics data help to reveal a complex, interconnected cellular landscape, and the analysis of omics data can highlight specific molecular features that may be implicated in a disease or biological condition [ 1 3 ]. In parallel with the proliferation of omics data, there exist large and expanding databases containing protein–protein interactions (PPI) [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%